Critical Success Factors for the Implementation of an EDRMS in the Government of The Gambia: A PMBOK 7th Edition Approach - Jallow, Fatoumatta Binta; Raharjo, Teguh; Trisnawaty, Ni Wayan (AI Society & STMIK Indonesia, 2025)
The successful implementation of an Electronic Document and Records Management System (EDRMS) in the public sector faces significant challenges, particularly in developing countries like The Gambia. Poor system integration, data security risks, resistance to change, and lack of leadership support hinder adoption. This study applies the PMBOK 7th Edition framework to identify critical success factors (CSFs) for EDRMS implementation. Using a Systematic Literature Review (SLR), this research analyzes key factors, including system compatibility, cybersecurity, legal compliance, and stakeholder engagement. Findings indicate that a structured project management approach enhances adoption by ensuring effective integration, risk mitigation, and user acceptance. The study provides practical recommendations for policymakers and IT managers to optimize digital record management strategies. Future research should explore case studies and emerging technologies such as AI and blockchain to strengthen EDRMS adoption.